IMPLEMENTASI MARKETING MIX DALAM UPAYA KEMAJUAN USAHA BUTIK MUSLIMAH DI KOTA LANGSA - febi febi; Syamsul Rizal; Chahayu Astina; Nurul Fajri; Fatahillah; Lili Apriliani (JIM: Jurnal Ilmiah Mahasiswa, 2019)
Aceh, as the province that became the pioneer of the implementation of Islamic Sharia in Indonesia. The need for Muslim dress or muslimah is an absolutely necessary thing. The need for Muslim clothing for the community encourages entrepreneurs to sell their best products are no exception with boutique entrepreneurs, especially in the city directly. Universally, goods sold in boutiques are very rare or even never found in ordinary stores. All that can not be separated because the boutique has a philosophy on the clothing items are exclusive, elite, fashionable and sophisticated fashion and complete with accessories. As for the problems in this study are (1) how the business boutique Muslim Langsa City. (2) how is the implementation of marketing mix in the effort of progress of Muslim clothing boutique in Langsa City ?. Based on these problems, this study aims to determine the implementation of marketing mix in the effort of Muslim clothing business boutique in Langsa City. The research method that the writer use in this research are: qualitative descriptive ie presentation of research result through description of observation result, interview and documentation to see the implementation of marketing mix in effort of progress of boutique clothing fashion Muslim in Langsa City. Based on the results of research that: Muslim Boutique in Langsa City specialize marketing its products in some market segment especially for society which is Moslem, which 70% target is teenagers, the rest is public. In the implementation of marketing mix in the effort of progress of Muslim fashion boutique in Langsa City apply four elements, that is: products at Muslim Boutique in Langsa City focus on quality according to customer requirement that put forward kesyar'iannya. The pricing strategy determined by the Muslim Boutique in Langsa City is adjusted to total raw materials, production materials, all manufacturing costs are totaled and profitability of each product is taken at 40%. In the distribution strategy set the business near the city center, universities, companies, and government buildings city of Langsa City is not far from the crowd. Boutique Muslimah in Langsa City in the selection of promotion strategies Muslim Boutique in Langsa City has made various promotions including, personal selling, advertising, sale promotion and publicity.